Stability analysis for delayed quaternion-valued neural networks via nonlinear measure approach - Tu, Zhengwen; Cao, Jinde; Alsaedi, Ahmed; Ahmad, Bashir (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, the existence and stability analysis of the quaternion-valued neural networks (QVNNs) with time delay are considered. Firstly, the QVNNs are equivalently transformed into four real-valued systems. Then, based on the Lyapunov theory, nonlinear measure approach, and inequality technique, some sufficient criteria are derived to ensure the existence and uniqueness of the equilibrium point as well as global stability of delayed QVNNs. In addition, the provided criteria are presented in the form of linear matrix inequality (LMI), which can be easily checked by LMI toolbox in MATLAB. Finally, two simulation examples are demonstrated to verify the effectiveness of obtained results. Moreover, the less conservatism of the obtained results is also showed by two comparison examples.
Keywords: quaternion-valued neural networks (QVNNs); stability; nonlinear measure approach; linear matrix inequality